The Consequences of Neoliberalism in the Current Pandemic - Navarro, Vicente (Int J Health Serv, 2020)
This article analyzes how the neoliberal policies, such as the politics of austerity (with considerable cuts to social policy expenditures including medical care and public health services) and the privatization of health services, imposed by many governments on both sides of the North Atlantic, considerably weakened the capacity of the response to the coronavirus pandemic in Italy, Spain, and the United States.